Design of the Missile Attitude Controller Based on the Active Disturbance Rejection Control - Shanzhong Liu; Mengqi Xue; Yaolong Qiu; Xingyu Zhou; Qingxiu Zhao (Journal of Aerospace Technology and Management, 2022)
Targeting at the stable tracking control problem of the interceptor missile’s flight attitude in the terminal guidance phase, the nonlinear mathematical model of missile attitude is used as the research object, in which the coupling among the channels is considered. The control strategies of Proportion Differentiation (PD) control, nonlinear and linear active disturbance rejection control are studied. Firstly, the expanded state observer is designed to estimate the total disturbance information in real time, and the error feedback controller is designed to provide disturbance compensation, so that the original second-order nonlinear system is decoupled into the canonical form of cascade integrators to realize the stable tracking control of the missile attitude. Secondly, the three-channel coupling closed-loop control system model is established, and under the influence of external disturbance and model parameter perturbation, the comparison between the three control methods is demonstrated by simulations. The simulation results show that these three methods can stabilize the missile attitude and track the reference input signal. Among them, the nonlinear active disturbance rejection control has the smallest overshoot, the strongest antiinterference ability, and better robustness.